2017
DOI: 10.3201/eid2307.170163
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pestivirus Species in Pigs, Austria, 2015

Abstract: A novel pestivirus species was discovered in a piglet-producing farm in Austria during virologic examinations of congenital tremor cases. The emergence of this novel pestivirus species, provisionally termed Linda virus, in domestic pigs may have implications for classical swine fever virus surveillance and porcine health management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 14 publications
4
87
0
5
Order By: Relevance
“…Nucleotide sequencing of the partial NS5B region of APPV of these samples revealed that they are closely related to strains from the United States (Arruda et al., ; Hause et al., ) and Germany (Beer et al., ). Moreover, the histological findings were similar to previous findings (Lamp et al., ; Postel et al., ) showing vacuolization of the white matter of the cerebellum. The new data will allow further investigations to explore the actual distribution and impact of these new putative pestivirus species.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nucleotide sequencing of the partial NS5B region of APPV of these samples revealed that they are closely related to strains from the United States (Arruda et al., ; Hause et al., ) and Germany (Beer et al., ). Moreover, the histological findings were similar to previous findings (Lamp et al., ; Postel et al., ) showing vacuolization of the white matter of the cerebellum. The new data will allow further investigations to explore the actual distribution and impact of these new putative pestivirus species.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we analysed serum and tissue samples of piglets displaying CT A‐II clinical signs from two farrow‐to‐wean farms located in Southern Brazil where APPV was detected employing RT‐PCR followed by DNA sequencing. Tissue samples were also examined by histopathology (Figure ), and histological findings similar to those previously reported in APPV and LINDA virus‐affected piglets (Lamp et al., ; Postel et al., ) were observed. Vacuolization of the white matter and myelin loss has been already described in animals affected by other pestiviruses, such as lambs and calves with BD‐ and BVDV‐congenital infections, respectively (Barlow, ; Montgomery, Van Olphen, Van Campen, & Hansen, ) and in CSFV (Emerson & Delez, ) and LINDA virus‐affected pigs (Lamp et al., ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Over the past decades, new members of pestiviruses have frequently been found in a number of domestic and wild animal species with different clinical manifestations or without clinical signs. These unclassified new members include Bungowannah virus, pestivirus of the giraffe, sheep pestivirus (Aydin‐like), rat pestivirus, Pronghorn antelope virus, atypical ruminant pestivirus (Hobi‐like; BVDV3), atypical porcine pestivirus (APPV), and Lateral‐shaking Inducing Neurodegenerative Agent (Linda) virus (Figure ) . The whole genome sequences among the pestivirus species are more than 25% divergent, which has been used for demarcation of a new species in the genus.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the atypical pestiviruses, Bungowannah virus has been identified to cause cardiac failure, stillbirth, and sudden death in piglets in Austria without clinical signs of congenital tremor (CT) . Recently, two other atypical pestiviruses, APPV and Linda virus, were reported to be associated with CT in piglets . Phylogenetic analysis has shown that these atypical pestiviruses (Bungowannah virus, Linda virus, and APPV) are highly divergent from the other members.…”
Section: Introductionmentioning
confidence: 99%